6β-Hydroxytestosterone, a Cytochrome P450 1B1 Metabolite of Testosterone, Contributes to Angiotensin II–Induced Hypertension and Its Pathogenesis in Male Mice. Issue 6 (June 2015) - Pingili, Ajeeth K.; Kara, Mehmet; Khan, Nayaab S.; Estes, Anne M.; Lin, Zongtao; Li, Wei; Gonzalez, Frank J.; Malik, Kafait U.
Abstract : Previously, we showed that Cyp1b1 gene disruption minimizes angiotensin II–induced hypertension and associated pathophysiological changes in male mice. This study was conducted to test the hypothesis that cytochrome P450 1B1-generated metabolites of testosterone, 6β-hydroxytestosterone and 16α-hydroxytestosterone, contribute to angiotensin II–induced hypertension and its pathogenesis. Angiotensin II infusion for 2 weeks increased cardiac cytochrome P450 1B1 activity and plasma levels of 6β-hydroxytestosterone, but not 16α-hydroxytestosterone, in Cyp1b1 +/+ mice without altering Cyp1b1 gene expression; these effects of angiotensin II were not observed in Cyp1b1 −/− mice. Angiotensin II–induced increase in systolic blood pressure and associated cardiac hypertrophy, and fibrosis, measured by intracardiac accumulation of α-smooth muscle actin, collagen, and transforming growth factor-β, and increased nicotinamide adenine dinucleotide phosphate oxidase activity and production of reactive oxygen species; these changes were minimized in Cyp1b1 −/− or castrated Cyp1b1 +/+ mice, and restored by treatment with 6β-hydroxytestoterone. In Cyp1b1 +/+ mice, 6β-hydroxytestosterone did not alter the angiotensin II–induced increase in systolic blood pressure; the basal systolic blood pressure was also not affected by this agent in either genotype. Angiotensin II or castration did not alter cardiac, angiotensin II type 1 receptor, angiotensin-converting enzyme, Mas receptor, or androgen receptor mRNA levels in Cyp1b1 +/+ or in Cyp1b1 −/− mice. These data suggest that the testosterone metabolite, 6β-hydroxytestosterone, contributes to angiotensin II–induced hypertension and associated cardiac pathogenesis in male mice, most probably by acting as a permissive factor. Moreover, cytochrome P450 1B1 could serve as a novel target for developing agents for treating renin–angiotensin and testosterone-dependent hypertension and associated pathogenesis in males. Abstract : Supplemental Digital Content is available in the text.